2021
DOI: 10.3390/nu13114065
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Nifli, A.-P. Comment on “Rosell-Cardona et al. Dietary Spray-Dried Porcine Plasma Reduces Neuropathological Alzheimer’s Disease Hallmarks in SAMP8 Mice. Nutrients 2021, 13, 2369”

Abstract: Thank you for your comments on our recent work of the effects of supplementation with spray-dried porcine plasma (SDP) on neuropathological markers of Alzheimer’s disease (AD) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Mechanisms of communication between the gut microbiota and brain primarily involve the regulation of the immune system and the activation of neural and endocrine pathways by the gut microbiota or its by-products [ 31 ]. Dietary supplementation with SDP improves brain resilience against the neuropathological hallmarks of AD [ 15 ] and prevents the cognitive decline in SAMP8 mice [ 19 ]. Previous studies have shown that SDP supplementation has anti-inflammatory properties because it can modulate the mucosal immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of communication between the gut microbiota and brain primarily involve the regulation of the immune system and the activation of neural and endocrine pathways by the gut microbiota or its by-products [ 31 ]. Dietary supplementation with SDP improves brain resilience against the neuropathological hallmarks of AD [ 15 ] and prevents the cognitive decline in SAMP8 mice [ 19 ]. Previous studies have shown that SDP supplementation has anti-inflammatory properties because it can modulate the mucosal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Spray-dried porcine plasma (SDP) is a functional protein source that contents many functional components such as albumin, immunoglobulins, transferrin, fibrinogen, growth factors and many other peptides that not only promote intestinal function but also have systemic effects beyond the intestine, such as on the respiratory and reproductive systems [ 15 , 16 , 17 , 18 ]. Using aged senescence-accelerated prone (SAMP8) mice, we have previously shown that dietary supplementation with SDP prevents cognitive decline and reduces neuroinflammation and oxidative stress in the central nervous system [ 19 ] and decreases the neuropathological hallmarks of AD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%